Poligami Dalam Perspektif Filsafat Hukum Islam (Kritik Terhadap Hukum Perkawinan Di Indonesia) - Husni fatimah; putri, putri nur Rahmadhani (Tabayyun : Journal Of Islamic Studies, 2024)
Polygamy is not a foreign phenomenon anymore, many people practice polygamy whether they have more than two or three wives. However, behind it there is strong criticism from many experts and indeed this is allowed by Islam. However, this study will examine the existing criticisms in the perspective of Islamic Law, whose data is obtained through several previous studies, this study aims to take a new perspective on polygamy that occurs in Indonesia. Keywords: Polygamy, Islamic law, Indonesia, marriage